2021
DOI: 10.1111/asj.13610
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and electroencephalographic changes in goats subjected to transportation, lairage, and slaughter

Abstract: This preliminary trial investigated the effect of transportation and lairage periods on physiological parameters of goats subjected to slaughter. Nine male Boer cross goats aged 8-12 months were transported for 6 h and kept at lairage for 3, 6, or 16 h (n = 3). Blood samples were collected at pre-(pre-T) and post-transportation (post-T), and post-slaughter (post-S) for determination of hematological parameters, serum enzyme, protein, and cortisol concentrations. Electroencephalogram readings were taken at pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The plasma ALT concentration recorded an increasing trend in goats under stressful conditions such as weaning stress ( 40 ), preslaughter transportation stress ( 41 ), and heat stress ( 42 ). Similar to the present study, increased plasma concentrations of CK in goats were observed ( 43 ) during preslaughter transportation stress and increased CK and LDH concentrations due to slaughter stress ( 44 ).…”
Section: Resultssupporting
confidence: 89%
“…The plasma ALT concentration recorded an increasing trend in goats under stressful conditions such as weaning stress ( 40 ), preslaughter transportation stress ( 41 ), and heat stress ( 42 ). Similar to the present study, increased plasma concentrations of CK in goats were observed ( 43 ) during preslaughter transportation stress and increased CK and LDH concentrations due to slaughter stress ( 44 ).…”
Section: Resultssupporting
confidence: 89%
“…In humans, a higher beta power was recorded under stressful conditions [ 42 ]. Several studies have recorded an increase in the beta waves during stress in animals such as during the transportation and slaughter of goats [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a technology used to measure the electric activity of neurons in the cerebrocortical region of the brain by fixing electrodes on various positions of the brain [ 28 , 29 ]. The electric activity of neurons was used to assess pain and stress in animal welfare during the slaughter process in goats [ 30 , 31 , 32 , 33 ]. However, the high cost of equipment, experimental conditions, and analysis still remain issues in its popularization.…”
Section: Introductionmentioning
confidence: 99%
“…The transportation and lairage stay have an essential effect on the various physiological parameters. Othman et al [ 127 ] studied the effect of lairage stay (3, 6, 16 h) and transportation duration (6 h) on various physiological and EEG changes during the halal slaughter of goats in Malaysia. The authors observed increased stress leukogram, hematocrit, total proteins, and muscle enzyme concentrations and a significantly decreased ( p < 0.05) Ptot value compared to their baseline counterparts.…”
Section: Eeg Application In Preslaughter Managementmentioning
confidence: 99%
“…After the lairage stay, these measurements became less significant, indicating recovery from transit stress. The authors [ 127 ] recommend a minimum 3-h lairage stay for goats transported for 6 h before slaughter.…”
Section: Eeg Application In Preslaughter Managementmentioning
confidence: 99%